Curriculist god- a documentary analysis on the idea of body, formation and man, in the curriculum of physical education in basic primary in religious i. E. (2022)
Physical Education curriculum throughout history have been accompanied by different political, economic, social and religious positions, this has led to the fact that, currently, and based on the evaluation exams that are carried out annually (such as the ICFES tests), private and religious educational institutions are the ones that postulate the type of man, body and training that they consider best. In the same way, these educational institutions through their curricula show their different ideological positions, especially about the body. However, the main objective of this research is to interpret the idea of the body that exists in curriculum of the 45 best institutions (according to Sapiens Research), in the city of Medellín, this will be done through the conceptual framework of Pedraza, Z. (2010), Bollnow, O.F. (2005) and Da Silva, T.T. (2001). The methodology has a mixed approach, accompanied by a content analysis as a method and a documentary systematization as a technique. An important finding is that the body for these educational institutions is unilateral, that is, it is understood from the curriculum as a tool, temple or machine, in addition, the distinction between the sexes continues to exist when developing the curriculum in the area of education physical.